Réponses

2014-10-30T13:12:26+01:00
C = ( 3sc + 1 )² -36
c = 9sc² +6sc +1 -36
c = 9sc² +6sc -35

factoriser

C = ( 3sc + 1 )² -36
C = ( 3sc + 1 )² -6²
c = (3sc+1 -6)(3sc +1 +6)
c= (3sc -5) (3sc +7)

C = ( 3sc + 1 )² -36
c = 9sc² +6sc -35
c = 9*(-1/3)² + 6* -1/3 -35
c = 9 * 1/9  -6/3 -35
c =  9/9 -6/3 -35
c = 1 -2 -35
c = -36

résoudre l'equation ( 3sc+ 7 ) ( 3sc - 5 ) = 0

3sc +7 = 0                3sc-5 =0
3sc =  -7                    3sc = 5
sc =  -7/3                      sc  = 5/3  




tu peut détailler : C = ( 3sc + 1 )² -36
c = 9sc² +6sc -35
c = 9*(-1/3)² + 6* -1/3 -35
c = 9 * 1/9 -6/3 -35
c = 9/9 -6/3 -35
c = 1 -2 -35
c = -36
stp c urgent